ANALISIS GAYA KEPEMIMPINAN WALIKOTA PADA SEKRETARIAT DAERAH (SEKDA) KOTA TIDORE KEPULAUAN - Kaidir, Iriyani Abd. (Jurnal Ilmiah Ecosystem, 2016)
Regional autonomy policy as one that related much with this research is aboutthe leadership style in Regional Secretariat of municipal government of Tidore Isles.Start out from such thing particularly type of leadership of a Mayor as chief ofgovernmental is very important to be applied in bureaucracy scope. Then focus andaim of this research to know how extensive of the leadership style in RegionalSecretariat of Municipal government city of Tidore Isles. Type of this research isqualitative descriptive, and research location that is Regional Secretariat (SEKDA)of Municipal government city of Tidore Isles. Data collecting process done usingobservation technique, interview, and documentation. While data analysis that usedwith data simplification reduction phase, data presentation and data conclusion.Data validation technique through persistence improvement, loyalty andprecise.Result of this research indicating that style leadership of a Mayor isoutstanding and applied in Regional Secretariat of Municipal government city ofTidore Isles are paternalistic, get participated in other leadership type namelycharismatic, transformational, and situational. Implementation type of a Mayorleadership is very influential for success of Municipal government city of TidoreIsles.